The profile of major congenital abnormalities in the United Arab Emirates (UAE) population. Issue 1 (January 1995) - al-Gazali, L I; Dawodu, A H; Sabarinathan, K; Varghese, M
Abstract : The aim of this study was to establish the profile of major congenital malformations in the United Arab Emirates (UAE) population which has a high rate of consanguinity. All births with birth weight above 500 g in the three hospitals in the Al Ain Medical District of UAE were prospectively studied from January 1992 to January 1994. About 98% of the births in the district occur in these three hospitals. Detailed family history and clinical and relevant laboratory investigations were recorded in each case. Necropsy was not permitted. The major malformations were classified as multiple or isolated single system abnormalities as well as genetic or non-genetic disorders. Of the 16, 419 births which occurred during the two year period, 173 (10.5/1000 births) had major malformations, 90 (52%) had multiple malformations, and 83 (47.97%) had involvement of a single system. Of the infants with multiple malformations, 43 had recognised syndromes, most of which are autosomal recessive disorders with a high frequency of rare syndromes. Twenty eight (31%) had chromosomal abnormalities. The most common systems involved in infants with isolated single system malformations include gastrointestinal (33), central nervous system (17), and cardiovascular (10). While the consanguinity rate was similar (57% v 54%), the frequency of first cousin marriages was much higher (51% v 30%) in the study group compared with the figures for the general population. The consanguinity rate was highest among the syndrome cases, and related parents were more likely to have infants with multiple malformations than an isolated single system abnormality with a relative risk of 1.69 (95% CL 1.27-2.24). Genetic factors could be implicated in 116 (67%) of the 173 cases of major malformations and 49 (28%) were potentially preventable. The study suggests that genetic disorders account for a significant proportion of congenital malformation in the UAE and, thus, a genetic service should be provided as part of the preventive cae programme.